Comparative genomics to uncover the secrets of tsetse and livestock-infective trypanosomes - Davila, A.M.R.; Majiwa, Phelix A.O.; Grisard, E.C.; Aksoy, S.; Melville, S.E. (Elsevier, 2003)
The pathogenic trypanosomes Trypanosoma vivax and Trypanosoma congolense are transmitted by tsetse and cause trypanosomosis, a debilitating disease affecting livestock in Africa and South America. Here, we discuss the need, relevance and advantage of having the Trypanosoma genomes sequenced, annotated and analyzed in a comparative genomics context. We also propose the increased involvement of scientists from endemic countries in the initiative to aid the development and maintenance of capacity in bioinformatics research in these countries.